Accelerated Chemical Shift Imaging of Hyperpolarized (13)C Metabolites - Wang, Jian-Xiong (Magn Reson Med, 2016)
PURPOSE: Chemical-shift imaging (CSI) has long been considered the gold standard method for in-vivo hyperpolarized (13)C metabolite imaging because of its high sensitivity. However, CSI requires a large number of excitations so it is desirable to reduce the number of RF excitations and the total acquisition time. METHODS: Centric phase encoding and 3D compressed sensing methods were adopted into a CSI acquisition to improve efficiency and reduce the number of excitations required for imaging hyperpolarized metabolites. The new method was implemented on a GE MR750W scanner for routine real time metabolic imaging experiments. RESULTS: Imaging results from phantoms and in-vivo animals using hyperpolarized (13)C tracers demonstrate that when the entire CSI data set is treated as a single object, compressed sensing can be satisfactorily applied to spectroscopic CSI. Centric k-space trajectory data collection also greatly improves the acquisition efficiency. This combination of compressed sensing CSI and acquisition time reduction was used to perform a hyperpolarized (13)C dynamic study. DISCUSSION: Compressed sensing can be satisfactorily applied to conventional CSI in hyperpolarized (13)C metabolite MR imaging to reduce the number of RF excitations and accelerate the imaging speed to take advantage of conventional CSI in providing high sensitivity and a large spectral bandwidth.